Interview with John Ackerman - Ackerman, John (2013)
1_setbukss Ackerman studied Russian/Soviet history at Stanford and has acquired, edited and published some of the seminal works in the fields of East-Central European and Russian/Soviet history and literature, including Ivo Banac's The National Question in Yugoslavia and With Stalin against Tito, Wendy Bracewell's The Uskoks of Senj, Roman Koropeckyj's Adam Mickiewicz, Mark Thompson's book on Danilo Kiš, Birth Certificate, Yuri Slezkine's Arctic Mirrors, Laura Engelstein's The Keys to Happiness, Lewis Siegelbaum's Cars for Comrades, and Valerie Kivelson's Cartographies of Tsardom. He has also published works by some of the younger scholars featured on this blog, including James Ward's biography of Jozef Tiso, Priest, Politician, Collaborator, and Claudia Verhoeven's The Odd Man Karakazov. Interview with John Ackerman, Director of Cornell University Press and the Europe and Russia/USSR acquisitions editor there. Interview conducted in Ithaca, NY on July 31, 2013.